Chronic and transient poverty and weather variability in the Philippines: Evidence using components approach - Connie Bayudan-Dacuycuy; Lora Kryz Baje (Philippine Institute for Development Studies (PIDS), 2017)
Weather is an integral part of our life and weather shocks can have severe implications on income and household consumption. Given evidence that points to altered patterns of weather parameters resulting from climate change, this paper aims to contribute to poverty studies in the Philippines by analyzing the effects of geographic attributes, like weather variability, on chronic and transient poverty. Based on the estimates of the generalized linear model, higher than normal rainfall contributes to a modest increase in chronic total and chronic food poverty in both urban and rural areas. In addition, asset ownership and college education have the most impact on the reduction of both types of poverty.
Keywords: 330; poverty dynamics; weather variability; components approach; Philippines